An Empirical Analysis of the Impact of Asset Management and Financing Decisions on Corporate Value - Alif Sepriadi; Athoriq Aulia Warena; Aulia Rahma; Dwi Amelia Putri; Suci Indah Sari (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2025)
This study analyzes the joint impact of asset management and financing decisions on corporate value, with financial performance as a mediating variable. Using financial data from the Central Statistics Agency (BPS) in 2023, the research focuses on Indonesia’s manufacturing, banking, and infrastructure sectors. Structural equation modeling (SEM) reveals that efficient asset management and balanced financing policies significantly improve firm value, both directly and indirectly through profitability. Sectoral results show that asset management has the strongest effect in manufacturing, while financing choices dominate in banking. These findings provide theoretical evidence of financial performance as a key transmission mechanism and practical insights for managers and regulators to align financial strategies with sector-specific needs. Future studies should extend the analysis with longitudinal data and governance-related variables to capture dynamic changes in corporate value creation.